The Right to Water: A Comparative Study of Law in Indonesia and South Africa - Imawan, Riswandha (Faculty of Law, Jambi University, 2023)
Water is essential for human life, so it cannot be denied that water has an important role in fulfilling other human rights, such as the right to life and the right to health. This implies the importance of good regulations related to water resources to ensure access and fulfillment of the right to water. This research seeks to answer the question of how regulations related to the right to water in Indonesia and South Africa compare, and most importantly whether these regulations are in accordance with international conventions, namely General Comment Number 15 on the Right to water. South Africa was chosen as a comparative country because its Constitution explicitly mentions the right to water for its people. This research was conducted using a comparative method of relevant laws related to the regulation of the right to water in Indonesia and South Africa. The results showed that Indonesia and South Africa have good regulations related to the right to clean water. Regulations related to water resources in both countries also support the efforts of both countries to fulfill the right to water.